Evaluación del comportamiento del escarabajo-plaga Strategus aloeus (coleoptera: scarabaeidae: dynastinae) frente a compuestos orgánicos volátiles que median su comunicación química. - Arias Puentes, Laura Daniela (Universidad Antonio Nariño, 2021)
In Colombia, the infestation of Strategus aloeus (Coleoptera, Scarabeidae) in young oil palms (Elaeis guineensis Jacq) produces damages that are reflected in economic losses on this crop of commercial interest. Different strategies have been used for its management, without obtaining satisfactory results. Taking into account the severity of the problem, it was proposed to evaluate the behavior of adult insects against volatile organic compounds that have been identified as possible mediators of their chemical communication. This study involved three stages: (1) Definition of the experimental conditions, (2) Evaluation of the behavior of the insect against the compounds, in the laboratory and (3) Statistical validation of the results obtained. From the first, the experimental conditions required for the evaluation of behavior under laboratory conditions were established. The bioassays in a "Y" olfactometer did not allow to establish differences of the adult S. aloeus insects against the evaluated odor sources: 2-butanone, 3-pentanone, sec-butyl acetate, and ethyl 4-methyloctanoate.